Early E. casseliflavus gut colonization and outcomes of allogeneic hematopoietic cell transplantation - Rashidi, Armin (PLoS One, 2019)
Gut dysbiosis has been associated with worse allogeneic hematopoietic cell transplantation (allo-HCT) outcomes. We reported an association between intrinsically vancomycin-resistant enterococci (iVRE: E. gallinarum and E. casseliflavus) gut colonization and lower post-transplant mortality. In this study, using an expanded cohort, we evaluated whether our previously observed association is species-specific. We included allo-HCT recipients with ≥1 positive rectal swab or stool culture for iVRE between days -14 and +14 of transplant. To investigate whether iVRE modulate the gut microbiota, we performed agar diffusion assays. To investigate whether iVRE differ in their ability to activate the aryl hydrocarbon receptor, we analyzed iVRE genomes for enzymes in the shikimate and tryptophan pathways. Sixty six (23 E. casseliflavus and 43 E. gallinarum) of the 908 allograft recipients (2011–2017) met our inclusion criteria. Overall survival was significantly higher in patients with E. casseliflavus (91% vs. 62% at 3 years, P = 0.04). In multivariable analysis, E. casseliflavus gut colonization was significantly associated with reduced all-cause mortality (hazard ratio 0.20, 95% confidence interval 0.04–0.91, P = 0.04). While agar assays were largely unremarkable, genome mining predicted that E. casseliflavus encodes a larger number of enzymes in the tryptophan metabolism pathway. In conclusion, E. casseliflavus gut colonization is associated with reduced post-HCT morality. Further research is needed to understand the mechanisms for this association.